IMPROVEMENT OF CITIZENS' PENSION SYSTEM UNDER THE INFLUENCE OF DEMOGRAPHIC AND ECONOMIC FACTORS BASED ON ECONOMETRIC MODELS - Bakhadir Safaralievich Mamatov (Scholars Digest Publishing, 2023)
The article studies the system of social protection, in particular, the issues of pension provision. The average monthly wages and pensions, and changes in the replacement rate in the pension system are analyzed. The methodology for determining the size of pensions and factors affecting the size of pensions are investigated. Based on the research results, proposals and recommendations for achieving a decent retirement have been developed.
Keywords: pension, pension provision, old-age pension, salary, seniority, pension fund, pensioner, pension, coverage ratio, demography, income, financial stability.